A multivariate analysis of shares listed on the Johannesburg Stock Exchange - Visser, Francesca (Department of Statistical Sciences, 2016)
This thesis examines the usefulness of multivariate statistical techniques to portfolio theory by applying two different multivariate techniques to two separate classificatory problems concerning shares listed on the Johannesburg Stock Exchange. In Chapter 1 the two techniques and two classificatory problems are introduced and their context within the general structure of portfolio theory is explained. Chapter 2 gives a theoretical overview of the first technique used, namely Factor Analysis. Chapters 3 and 4 discuss the application of factor analytic techniques to shares listed on the Johannesburg Stock Exchange. Chapter 5 gives a theoretical overview of Multiple Discriminant Analysis, the second multivariate technique used. Chapter 6 represents a survey of previous applications of Multiple Discriminant Analysis in the field of Finance, while Chapters 7 and 8 discuss the application of this technique to shares listed on the Johannesburg Stock Exchange. Finally, Chapter 9 gives a brief summary of the main conclusions in this thesis.